EFFECT OF BILINGUAL INSTRUCTIONAL METHOD IN THE ACADEMIC ACHIEVEMENT OF JUNIOR SECONDARY SCHOOL STUDENTS IN MATHEMATICS - Professor Steve Dele Oluwaniyi; Dr Benard Festus Azuka; Prof. Solomon Gboyega Ojo; Dr Festus Sunday Smart Oloda; Dr James Olatunji Jekayinfa; Dr Sylvester Orobosa Okwuosa (IJRDO- Journal of Educational Research, 2024)
The importance of mathematics in the modern society is overwhelming. The importance of mathematics has long been recognized all over the world, and that is why all students are required to study mathematics at the primary and secondary school levels, whether they have the aptitude for it or not (Ojo, 2015; Adebayo, 2008; Adeleke, 2007). However, despite the importance of mathematics in the Nigerian education system, the students’ performances continue to deteriorate year after year. Several reasons have been proffered for the high failure rate in mathematics. Given the options, many students will not offer mathematics (Agwagah, 2013). Agwagah noted that an increasing number of students find it difficult to do well in mathematics because of the teaching method used in teaching most of the themes are not interesting. In other words, the prime position accorded mathematics in the society is at risk because of persistent poor performance. According to Kurumeh and Achor (2008), the difficulties of students in learning mathematics could be attributed to the approach to which the contents are being presented to the students, the abstractness of mathematical concepts, and poor foundation, among others. Most students, especially, at the Junior Secondary School (JSS) have difficulties in understanding mathematics because of the language of instruction (which is English Language) (Ifeanacho, 2012). Majority of the students who are highly proficient in performing mathematical operations, in solving symbolic problems are less proficient in solving problems when it is algebraic (Iji, Abakpa, & Takor, 2015).In recent years, the language of instruction has become an active focus of investigation in education research, including research in mathematics education. Such focus is a symptom of a relatively recent paradigmatic shift whose main characteristics are a new understanding of the student and increasing awareness of the learning contexts, such as, notably the complexities arising from cultural and linguistic diversity (Radford & Barwell, 2022). When students’ conceptualizations are perceived to be incorrect, language is often then seen as an obstacle or barrier to the effective communication of the desired knowledge or structures. Language, however, is clearly more than a hindrance or an obstacle; language, talk, text and the production and interpretation of symbols are integral to the creation of learning, teaching and assessment, particularly in mathematics. The contributions of language, the politics of discourse, and critical studies, with most emphasis on the issue of multilingual classrooms need the urgent attention of education stakeholders. Multilingualism is the ability to speak two or more languages fluently. There are many benefits of multilingualism, such as improving cognitive, social, emotional, and economic skills. Multilingualism does not seem to have a significant impact on mathematical reasoning or problem-solving. However, multilingual students who are allowed to use many languages to discuss and solve problems have increased mathematical productivity, creativity, and problem-solving skills. Teachers working in a multilingual setting should be aware that the use of the first language may have a great influence on mathematics learning, especially when the students are involved in cognitively complex issues. The study of multilingual mathematics learners requires theoretical notions that address not only the cognitive and domain-specific aspects of learning mathematics but also the linguistic and cross-cultural nature of this work.Multilingualism has multiple benefits for students, such as giving them an academic advantage and improving their employment prospects once they leave school. Moreover, multilingualism gives them access to more than one culture and improves their understanding of different cultures and languages (Halai & Clarkson, 2016). Language plays a crucial role in learning amidst a multilingual classroom (Adetuyi, 2017). Essien (2018) opined that learning of mathematics is through language, and involves reading, writing, listening and discussion, all of which are heavily language-based activities. Natural language and language of mathematics play different roles. With their own specificities, each of them provides individuals with access to different layers of mathematical consciousness. They provide individuals with different forms of expressiveness and aesthetic experience. Several studies (e.g. Atweh, Bose, Graven, Subramanian & Venkat, 2014) noted the concerns about primary school students’ poor achievement in numeracy across many countries in Africa, Asia, and Latin America. Essien (2018) observed that various mathematics education research on multilingualism point to the intricate link between language competence and mathematics classroom practices. However, systematic review of literature on multilingualism (e.g. Setati, Chitera & Essien, 2009; Essien, 2018) found insignificant number of publications that focused on multilingual classroom practices and students’ achievement. In addition, research on the role of language in multilingual primary school level was insignificant compared to the role of language in mathematics at other levels of education. While literature has focused on pedagogical practices, role of language and conceptual framework necessary to support teaching and learning in a multilingual classroom ( e.g. Freeman & Freeman, 2014; Viesca & Teemant, 2019). Van Laren and Goba (2013) suggested that when teaching mathematics to second language students, teachers should introduce two languages simultaneously for clarity of the mathematical terms and concepts for good academic achievement. Kasma Suwanarak (2014) opined that balanced-language instruction to some extent promote academic achievement in bilingual students. Hence, the more bilingual experience and the more balanced exposure to both of their languages the students have, the more advantages they gain for promoting their learning success.The importance of language in the teaching and learning of mathematics can never be over emphasized. Teaching mathematics with two languages most especially with the local language can increase the rate of comprehension by the students. Different ways of understanding learning contribute to our knowledge of the relationship between language and mathematics in bilingual classrooms. According to Moschkovich, (2007) the relationship between language and mathematics in research began in the field of psychology and examined the cognitive functioning of bilingual learners during arithmetic computations and the solving of word problems.Achievement is the result, the successfulness, the extent or ability, the progress in learning educational experiences that the individual indicate in relation with his/her educational learning (Olga, 2008). Achievement in mathematics, which is the focus of this study, is viewed as a very important factor in teaching and learning of mathematics and it refers to students’ cognitive achievement and psychomotor skills, which are measured in terms of pass or fail (Adebayo, 2008; Popoola & Ajani, 2011). When achievement is below expectation, it is referred to as under-achievement or poor achievement. When students are successful in examination they will have the feeling of pride that they made success with their own efforts and skill. Small success can give students sense of achievement. On the other hand, persistent failure dampens students’ interest.